From simple-minded MDGs to muddle-headed SDGs*. (1st January 2018) - Vandemoortele, Jan
ABSTRACT: Respectable progress was made towards the Millennium Development Goals (MDGs). The challenge that remains is two-fold: environmental sustainability and high inequality. However, the Sustainable Development Goals (SDGs), to be reached by 2030, dodge these challenges because the relevant targets lack precision and clarity. Agenda 2030 is not universal in scope because the few targets that are verifiable – those that contain conceptual clarity, numerical outcome and specific deadlines – apply primarily to developing countries. The omission of targets for overweight/obesity and breastfeeding exemplifies the reluctance of developed countries to commit themselves to specific, quantitative and time-bound targets. Most SDG targets that are verifiable are actually not dissimilar from the MDGs. They clearly constitute a difficult intergovernmental compromise, made increasingly arduous by the deepening North–South divide, a return of East-West tensions, and a resurging sense of nationalism in several member states. To a large extent, the context of weak multilateralism explains why the SDGs are not fit for purpose to address the dual challenge of environmental sustainability and high inequality. The article concludes by proposing two vital steps to help realize their transformative potential.